Commentary on 'The arms of the chimeras' by Béatrice Ithier. (April 2016) - Abram, Jan
Abstract : In this Commentary I will first of all summarise my understanding of the proposal set out by Béatrice Ithier concerning her concept of the 'chimera'. The main part of my essay will focus on Ithier's claim that her concept of the chimera could be described as a 'mental squiggle' because it corresponds to Winnicott's work illustrated in his book 'Therapeutic Consultations' (1971). At the core of Ithier's chimera is the notion of a traumatic link between analyst and patient, which is the reason she enlists the work of Winnicott. I will argue, however, that Ithier's claim is based on a misperception of the theory that underpins Winnicott's therapeutic consultations because, different from Ithier's clinical examples of work with traumatised patients, Winnicott is careful to select cases who are from an 'average expectable environment' i.e. a good enough family. Moreover, Winnicott does not refer to any traumatic affinity with his patients, or to experiencing a quasi‐hallucinatory state of mind during the course of the consultations. These aspects are not incorporated into his theory. In contrast (to the concept Ithier attempts to advance), Winnicott's squiggle game constitutes an application of psychoanalysis intended as a diagnostic consultation. In that sense Winnicott's therapeutic consultations are comparable with the ordinary everyday work between analyst and analysand in a psychoanalytic treatment. My Commentary concludes with a question concerning the distinction between the ordinary countertransference in working with patients who are thinking symbolically in contrast to an extraordinary countertransference that I suggest is more likely to arise with patients who are traumatised and thus functioning at a borderline or psychotic level.